Non-fungible tokens (NFTs) : examining the impact on consumers and marketing strategies /: examining the impact on consumers and marketing strategies. (2022) - Sestino, Andrea; Guido, Gianluigi; Peluso, Alessandro M, 1978-
No abstract available